Bleeding events among patients concomitantly treated with direct oral anticoagulants and macrolide or fluoroquinolone antibiotics. Issue 2 (9th October 2022) - Yagi, Tatsuya; Mannheimer, Buster; Reutfors, Johan; Ursing, Johan; Giunta, Diego Hernan; Kieler, Helle; Linder, Marie
Abstract : Fluoroquinolones and macrolides may, due to a potential drug‐drug interaction, increase the concentration of any concomitantly administered direct oral anticoagulant (DOAC) and thereby increase the risk of severe bleeding. However, clinical evidence for such an effect is scarce. The present study aimed to evaluate the association between the use of fluoroquinolones or macrolides and bleeding events in patients with concomitant DOAC use. This was a nationwide cohort study including 19 288 users of DOACs in 2008‐2018 using information from Swedish national health registers. We compared the incidence of bleeding events associated with use of fluoroquinolones or macrolides using doxycycline as a negative control. Cox regression was used to calculate crude and adjusted hazard ratios (aHRs) in time windows of various length of follow‐up after the start of antibiotic use. The incidence rates for fluoroquinolones and macrolides ranged from 12 to 24 and from 12 to 53 bleeding events per 100 000 patients in the investigated time windows. The aHRs (95% confidence interval) for use of fluoroquinolones and macrolides were 1.29 (0.69‐2.44) and 2.60 (0.74‐9.08) at the concomitant window, 1.31 (0.84‐2.03) and 1.79 (0.75‐4.29) at 30 days, and 1.34 (0.99‐1.82) and 1.28 (0.62‐2.65) at 150 days, respectively. With regard to fluoroquinolones, the present study suggests that the risk of bleeding when combined with DOACs, if any, is small. Codispensation of macrolides in patients on DOACs was not associated with an increased risk of bleeding. However, due to the small number of macrolide users, the results must be interpreted with caution.